Task shifting healthcare services in the post-COVID world: A scoping review. - Shukanto Das; Liz Grant; Genevie Fernandes (PLOS Global Public Health)
Task shifting (TS) is the redistribution of healthcare services from specialised to less-qualified providers. Need for TS was intensified during COVID-19. We explore what impact TS had on service delivery during the pandemic and examine how the pandemic affected TS strategies globally. We searched five databases in October 2022, namely Medline, CINAHL Plus, Elsevier, Global Health and Google Scholar. 35 citations were selected following the PRISMA-ScR guidelines. We analysed data thematically and utilised the WHO health systems framework and emergent themes to frame findings. We uncovered instances of TS in countries across all income levels. 63% (n = 22) of the articles discussed the impact of TS on healthcare services. These encompassed services related to mental healthcare, HIV, sexual and reproductive health, nutrition and rheumatoid diseases. The remaining 37% (n = 13) focused on how the pandemic altered strategies for TS, particularly in services related to mental healthcare, HIV, hypertension, diabetes and emergency care. We also found that studies differed in how they reported TS, with majority using terms "task shifting", followed by "task sharing", "task shifting and sharing" and "task delegation". Our analysis demonstrates that TS had a substantial impact across healthcare systems. Modifying roles through training and collaboration strengthened workforce and enhanced diagnostic services. Strategic leadership played a crucial role in the process. More research on the financial aspects of TS during pandemics is required. Stakeholders generally accepted TS, but transferring staff between healthcare programs caused unintended disruptions. The pandemic reshaped TS, moving training, patient care and consultations to digital platforms. Virtual interventions showed promise, but digital access remained a challenge. Healthcare organisations adapted by modifying procedures, pathways and staff precautions. We recommend refining strategies for TS, and expanding on it to address workforce shortages, improve access, and enhance services, not only during crises but also beyond.